Hydraulic composition
Patent Information
- Application Number
- JP2022098281
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-17
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2042-06-17
AI Technical Summary
Existing geopolymer compositions face challenges in achieving both improved fluidity and strength of the cured product, with increasing water content leading to decreased strength and dispersants not effectively enhancing fluidity.
A hydraulic composition comprising fine aggregate, metasilicate, alumina-silica fine powder, hydrogen carbonate, and water, with specific ratios and mixing methods to balance fluidity and strength development.
The composition achieves both excellent fluidity and strength in the cured product, utilizing industrial by-products and contributing to sustainable development goals by reducing emissions.
Abstract
Description
[Technical Field]
[0001] The present invention relates to a hydraulic composition and a method for producing a hardened product thereof. [Background technology]
[0002] In recent years, in order to achieve the SDGs, there has been a push to develop environmentally friendly infrastructure from an ESG perspective, and technological development is underway regarding environmentally friendly hydraulic compositions that reduce the amount of CO2 emitted by cement during the firing of calcium carbonate.
[0003] As an example, hydraulic compositions called geopolymers, which are made by hardening ground granulated blast furnace slag containing silicates such as aluminum silicate using an alkaline solution, have been attracting attention.
[0004] Geopolymers harden through the dissolution of aluminum silicate by alkali and the formation of hydration products, so the more strongly alkaline stimulants such as sodium hydroxide or potassium hydroxide are used in combination, the better the strength they exhibit.
[0005] Patent Document 1 discloses the use of a mixture of sodium silicate and sodium carbonate as a hardening accelerator for geopolymers using alumina-silica fine powder.
[0006] Patent Document 2 discloses a bicarbonate-based hardener for silicate-based soil stabilization chemical solution, which contains, in a specified ratio, component a: sodium bicarbonate; component b: potassium bicarbonate; component c: at least one selected from the group consisting of powdered naphthalene sulfonic acid compounds, lignin sulfonic acid compounds, oxypolycarboxylic acid compounds, and melamine sulfonic acid compounds; and component d: alkali metal carbonate.
[0007] Patent Document 3 discloses a viscosity reducer for geopolymers containing a specific phosphate ester compound, an admixture for geopolymers containing the same, and a geopolymer-forming composition.
[0008] Patent Document 4 discloses a backfilling material that contains (a) slag or fly ash, (b) sodium aluminate, and (c) sodium silicate, in which the molar ratio of SiO to NaO in the sodium silicate is in the range of 0.9 to 2.7, the concentration of component (a) in the backfilling material is in the range of 5 to 50 mass%, the concentration of component (b) in the backfilling material is in the range of 10 to 45 mass%, and the concentration of the sodium silicate in the backfilling material is in the range of 10 to 28 mass%.
[0009] Furthermore, Non-Patent Document 1 discloses the definition, materials, mechanisms, challenges, and possibilities of geopolymers. Non-Patent Document 2 discloses a one-component geopolymer that does not use an alkaline solution and is made by blending alumina-silica fine powder, a powdered alkaline compound, and aggregate. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] US Patent Application Publication No. 2015 / 0321954 [Patent Document 2] Japanese Patent Application Laid-Open No. 2002-88365 [Patent Document 3] Japanese Patent Application Publication No. 2020-138899 [Patent Document 4] Japanese Patent Application Publication No. 2019-77798 [Non-patent literature]
[0011] [Non-Patent Document 1] Concrete Engineering, Vol. 56, No. 5, pp. 409-414, Japan Concrete Institute, May 2018 [Non-patent document 2] Cement and Concrete Research, Vol. 103, pp. 21-34, Elsevier BV, November 2017 Summary of the Invention [Problem to be solved by the invention]
[0012] However, applying a cement dispersant to a geopolymer composition does not improve the fluidity compared to a cement-based slurry, such as concrete. On the other hand, increasing the amount of water to improve the fluidity of a geopolymer composition reduces the strength of the hardened geopolymer.
[0013] The present invention provides a geopolymer-type hydraulic composition that has excellent fluidity and strength after hardening. [Means for solving the problem]
[0014] The present invention relates to a hydraulic composition containing (A) fine aggregate (hereinafter referred to as component (A)), (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder (hereinafter referred to as component (C)), (D) bicarbonate (hereinafter referred to as component (D)), and (E) water (hereinafter referred to as component (E)), wherein the content of component (D) is 0.5 to 50 parts by mass per 100 parts by mass of component (B).
[0015] The present invention also relates to a method for producing a hydraulic composition by mixing (A) fine aggregate, (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder, (D) bicarbonate (hereinafter referred to as component (D)), and (E) a component containing water, in which component (D) is mixed in an amount of 0.5 to 50 parts by mass per 100 parts by mass of component (B).
[0016] The present invention also provides a process for obtaining a hydraulic composition by mixing components including (A) fine aggregate, (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder (hereinafter referred to as component (C)), (D) bicarbonate (hereinafter referred to as component (D)), and (E) water (hereinafter referred to as component (E)), the process comprising: step (I) of mixing component (D) in an amount of 0.5 parts by mass to 50 parts by mass per 100 parts by mass of component (B); Step (II) of curing the hydraulic composition to obtain a hardened body; The present invention relates to a method for producing a cured body, including the steps of: [Effects of the Invention]
[0017] According to the present invention, a geopolymer type hydraulic composition having excellent fluidity and strength of the hardened product is provided. This invention contributes to the effective use of industrial by-products and waste and the reduction of CO2 emissions, and is therefore thought to be a technology that can contribute to the achievement of SDGs, such as goals 7, 9, 11, 12, and 13, which have been advocated in recent years to realize a sustainable society. DETAILED DESCRIPTION OF THE INVENTION
[0018] The present inventors have found that adding a predetermined amount of bicarbonate (component (D)) to a hydraulic composition containing fine aggregate, metasilicate, alumina-silica fine powder, and water improves the fluidity of the hydraulic composition and also enables the set product of the hydraulic composition to exhibit sufficient strength. The reason for this effect is not entirely clear, but is presumed to be as follows. As mentioned above, geopolymers are formed by the dissolution of aluminum silicate in alkali followed by the formation of hydration products. A typical hydration product that contributes to strength development is a complex of calcium, aluminum, and silicon oxides called CS(A)-H. This hydration product grows rapidly under high pH conditions and in the presence of dissolved calcium ions. The (D) component reversibly immobilizes and releases calcium ions as relatively soluble calcium bicarbonate, thereby suppressing the decrease in fluidity of the hydraulic slurry associated with the rapid growth of CS(A)-H during the early stages of hydration. It is believed that the (D) component releases calcium ions intermittently over time, promoting the hydration reaction. In the present invention, the content of (D) component within a specified range effectively realizes these effects, achieving both fluidity and strength development in the hardened body.
[0019] <Hydraulic composition> The hydraulic composition of the present invention contains fine aggregate (A), metasilicate (B), fine alumina-silica powder (C), a predetermined amount of hydrogen carbonate (D), and water (E).
[0020] Component (A) is a fine aggregate. Component (A) may be natural sand or artificial sand. Examples of natural sand include river sand, land sand, mountain sand, sea sand, lime sand, silica sand, chromite sand, zircon sand, olivine sand, alumina sand, natural lightweight fine aggregate, and crushed sands thereof. Examples of artificial sand include blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, recycled fine aggregate, synthetic mullite sand, SiO2-based artificial sand whose main component is SiO2, Al2O3-based artificial sand whose main component is Al2O3, SiO2 / Al2O3-based artificial sand, SiO2 / MgO-based artificial sand, SiO2 / Al2O3 / ZrO2-based artificial sand, SiO2 / Al2O3 / Fe2O3-based artificial sand, etc. Here, the main component refers to the component that is most abundant among the components contained in the sand. These may be used alone or in combination of two or more.
[0021] Component (A) is preferably at least one selected from river sand, land sand, mountain sand, sea sand, lime sand, silica sand, blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, natural lightweight fine aggregate, and recycled fine aggregate. These may be crushed sand.
[0022] From the viewpoint of the workability of the hydraulic composition (hydraulic slurry), the degree of amorphization of the fine aggregate is preferably 30% or less, more preferably 20% or less, even more preferably 10% or less, and even more preferably 5% or less. The lower limit of the degree of amorphization of the fine aggregate is not limited, but may be, for example, 0% or more, or 1% or more.
[0023] There are various methods for controlling the degree of amorphization of component (A), but it is generally preferable to use a manufacturing method that rapidly cools a molten material. For example, there is a method in which the raw material is melted and rapidly cooled by air-breaking, or a method in which it is treated in a flame and rapidly cooled. In either case, the cooling method may be selected appropriately at various speeds depending on the material and particle size. Another possible method is to amorphize a material that has been crystallized by heat treatment and cooling treatment. Among these, the flame fusion method, which allows for easy control of heating and cooling, is preferred.
[0024] The degree of amorphousness of component (A) can be determined by the X-ray diffraction method shown below. The fine aggregate was crushed in a mortar and pressed onto an X-ray glass holder of a powder X-ray diffractometer. The powder X-ray diffractometer used was a Rigaku MultiFlex (CuKα radiation source, 40 kV tube voltage, 40 mA tube current) with a scan interval of 0.01°, a scan rate of 2° / min, and slits DS1, SS1, and RS0.3 mm, over the 2θ range of 5° to 90°. A straight line was drawn connecting the X-ray intensities at low and high angles over the 2θ range of 10° to 50°. The area under the line was used as the background. The crystallinity was calculated using the instrument's software and subtracted from 100 to obtain the amorphousness. Specifically, the amorphous peak (halo) and each crystalline component were separated by curve fitting for the area above the background, and their respective areas were determined. The amorphousness (%) was calculated using the following formula: Amorphous ratio (%) = halo area / (crystalline component area + halo area) × 100
[0025] Component (A) is preferably spherical from the viewpoint of improving the fluidity of the hydraulic composition. Here, spherical in this embodiment refers to a round shape like a ball, and more specifically, refers to a shape having a sphericity of preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, even more preferably 0.95 or more, and even more preferably 0.97 or more. It is preferable from the viewpoint of fluidity that the sphericity of the fine aggregate in this embodiment is equal to or greater than the above-mentioned lower limit. Furthermore, it is also preferable from the viewpoint of a smoother surface that the sphericity of the fine aggregate in this embodiment is equal to or greater than the above-mentioned lower limit. The upper limit of the sphericity is specifically 1 or less.
[0026] The sphericity of component (A) is determined by analyzing the image (photograph) of the particles taken with an optical microscope or a digital scope (for example, Keyence VH-8000) to determine the area of the projected cross section of the particle and the perimeter of the cross section, and then calculating the projected cross section area (mm 2 The particle diameter can be calculated by dividing the circumference (mm) of a perfect circle with the same area as the particle by the circumference (mm) of the particle's projected cross section, and then averaging the values obtained for any 50 particles.
[0027] The average particle size of component (A) is preferably 0.1 mm or more, more preferably 0.5 mm or more, from the viewpoint of the workability of the hydraulic composition, and is preferably 5.0 mm or less, more preferably 2.0 mm or less, and even more preferably 1.0 mm or less, from the viewpoint of the workability of the hydraulic composition. The average particle size of the component (A) can be measured by the following method.
[0028] (Method for measuring average particle size) If the sphericity of the particle's projected cross section is 1, the diameter (mm) is measured; on the other hand, if the sphericity is less than 1, the major axis diameter (mm) and minor axis diameter (mm) of randomly oriented particles are measured and (major axis diameter + minor axis diameter) / 2 is calculated, and the average value obtained for 100 randomly selected particles is used as the average particle size (mm). The major axis diameter and minor axis diameter are defined as follows: When a particle is stabilized on a flat surface and the projected image of the particle on the flat surface is sandwiched between two parallel lines, the width of the particle at the smallest distance between the parallel lines is called the minor axis diameter, and the distance when the particle is sandwiched between two parallel lines perpendicular to the parallel lines is called the major axis diameter. The major axis diameter and minor axis diameter of a particle can be determined by taking an image (photograph) of the particle using an optical microscope or a digital scope (for example, Keyence VH-8000 model) and analyzing the obtained image.
[0029] The hydraulic composition of the present invention may contain, relative to 100 parts by mass of the composition, for example, 10 parts by mass or more, further 20 parts by mass or more, or further 30 parts by mass or more of component (A) from the viewpoint of the strength development of the set product of the hydraulic composition, and 90 parts by mass or less, further 80 parts by mass or less, or further 70 parts by mass or less from the viewpoint of the workability of the hydraulic composition.
[0030] Next, the metasilicate of component (B) will be described. Examples of metasilicate salts include concentrated aqueous solutions of sodium metasilicate, known as water glass (e.g., composition formula Na2SiO3·nH2O, n = 1.3 to 4.0). Other examples include solid metasilicate hydrates such as sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, potassium metasilicate pentahydrate, potassium metasilicate nonahydrate, and magnesium metasilicate pentahydrate. Component (B) is preferably at least one selected from water glass, sodium metasilicate pentahydrate, and sodium metasilicate nonahydrate.
[0031] The hydraulic composition of the present invention may contain, for example, 0.1 part by mass or more, further 0.5 part by mass or more, further 1.0 part by mass or more of component (B) relative to 100 parts by mass of the composition, from the viewpoint of the strength development of the cured product of the hydraulic composition.
[0032] From the viewpoint of the strength development of the cured product of the hydraulic composition, the content of the component (B) in the hydraulic composition of the present invention may be, for example, 0.5 parts by mass or more, preferably 1.0 part by mass or more, more preferably 2 parts by mass or more, even more preferably 2.5 parts by mass or more, and still more preferably 5 parts by mass or more, per 100 parts by mass of the component (A), and may be, for example, 50 parts by mass or less, preferably 35 parts by mass or less, and more preferably 20 parts by mass or less.
[0033] Next, the alumina-silica fine powder of component (C) will be described. Component (C) can be a fine powder containing aluminosilicate (xM2O·yAl2O3·zSiO2·nH2O, where M is an alkali metal). Component (C) dissolves cations such as aluminum and silicon upon contact with an alkaline compound and / or its aqueous solution, and acts as a supply source of these cations.
[0034] The molar ratio of alumina (Al2O3) to silica (SiO2) in component (C) may be, for example, 0.05 or more, or even 0.10 or more, and 1.00 or less, or even 0.50 or less, in terms of the strength development of the hardened body of the hydraulic composition.
[0035] Suitable examples of the alumina-silica fine powder of component (C) include 1) industrial waste and by-products such as ground granulated blast furnace slag, fly ash, clinker ash, fluidized bed coal ash, ground granulated molten slag from municipal waste incineration ash, red mud, and ground granulated molten slag from sewage sludge incineration ash, 2) natural aluminosilicate minerals and clays such as metakaolin and their fired products, and 3) volcanic ash. Of these, the industrial waste of 1) above is particularly suitable because, compared to the other components, there are no restrictions on the place of origin and it also leads to the effective use of industrial waste resources.
[0036] Component (C) may be one or more selected from ground granulated blast furnace slag, fly ash, metakaolin, rice husk incineration ash, coconut husk incineration ash, municipal waste incineration ash, and sewage sludge incineration ash. Component (C) is preferably one or more selected from ground granulated blast furnace slag and fly ash.
[0037] In the present invention, two or more types of component (C) can be used. In the present invention, when two or more types of component (C) are used, for example, when two or more types selected from ground granulated blast furnace slag, fly ash, metakaolin, rice husk incineration ash, coconut shell incineration ash, municipal waste incineration ash, and sewage sludge incineration ash are used as component (C), the hydraulic composition of the present invention preferably contains ground granulated blast furnace slag as component (C) from the viewpoint of strength development of the set body of the hydraulic composition.
[0038] When the hydraulic composition of the present invention contains two or more types of component (C), and contains ground granulated blast furnace slag as component (C), from the viewpoint of the strength development of the set body of the hydraulic composition, the ratio of ground granulated blast furnace slag in component (C) is, for example, 5 parts by mass or more, preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and for example, 90 parts by mass or less, preferably 70 parts by mass or less, more preferably 50 parts by mass or less, per 100 parts by mass of component (C). The hydraulic composition of the present invention preferably contains, as components (C), (C1) ground granulated blast furnace slag and (C2) one or more selected from fly ash, metakaolin, rice husk incineration ash, coconut husk incineration ash, municipal waste incineration ash, and sewage sludge incineration ash.
[0039] Ground granulated blast furnace slag is a by-product of refining iron in a blast furnace, and is primarily composed of calcium oxide (CaO), silica (SiO2), and alumina (Al2O3), and is specified in JIS A 6206. In the present invention, the ground granulated blast furnace slag particularly used preferably has a CaO content in the range of 30% by mass to 60% by mass. Fly ash is primarily composed of silica (SiO2) and alumina (Al2O3), and is classified into Classes I to IV (JIS A6201) based on particle size and flow value. JIS Classes I and II, which have fine particle size and high reactivity, are suitable. The CaO content in fly ash may be 10.1% by mass or less.
[0040] (C) component is the Blaine specific surface area (cm 2 / g) is, from the viewpoint of the strength development of the set body of the hydraulic slurry, for example, 1,500 or more, preferably 2,000 or more, more preferably 2,500 or more, even more preferably 3,000 or more, and still more preferably 3,500 or more, and from the viewpoint of the handleability of the powdery hydraulic composition, for example, 8,000 or less, preferably 7,500 or less, more preferably 7,000 or less, even more preferably 6,500 or less, and still more preferably 6,000 or less. The Blaine specific surface area of component (C) is measured and calculated using a Blaine air permeability apparatus specified in JIS R 5201.
[0041] The hydraulic composition of the present invention may contain, for example, 5 parts by mass or more, further 10 parts by mass or more, further 20 parts by mass or more, and 60 parts by mass or less, further 50 parts by mass or less, further 40 parts by mass or less of the component (C) relative to 100 parts by mass of the composition, from the viewpoint of the strength development of the cured product of the hydraulic composition.
[0042] Component (D) is bicarbonate. Examples of component (D) include hydrogen carbonates and alkali metal hydrogen carbonates. Examples of hydrogen carbonates include potassium hydrogen carbonate and sodium hydrogen carbonate. The carbonates are preferably solid.
[0043] In view of the fluidity of the hydraulic composition slurry, the content of the component (D) in the hydraulic composition of the present invention is 0.5 parts by mass or more, preferably 1.0 part by mass or more, more preferably 5.0 parts by mass or more, and 50 parts by mass or less, preferably 45 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 25 parts by mass or less, per 100 parts by mass of the component (B).
[0044] The hydraulic composition of the present invention may contain, for example, 0.1 part by mass or more, further 0.2 part by mass or more, further 0.4 part by mass or more, and 4.0 parts by mass or less, further 2.0 parts by mass or less, or further 1.0 part by mass or less of the component (D) relative to 100 parts by mass of the composition, from the viewpoint of fluidity of the hydraulic composition slurry.
[0045] The component (E) is water. The hydraulic composition of the present invention may contain, relative to 100 parts by mass of the composition, for example, 1.0 part by mass or more, further 3.0 parts by mass or more, or even 5.0 parts by mass or more of the component (E) from the viewpoint of the workability of the hydraulic composition, and 45.0 parts by mass or less, further 30.0 parts by mass or less, or even 15.0 parts by mass or less from the viewpoint of the strength development of the set product of the hydraulic composition.
[0046] The hydraulic composition of the present invention may contain optional components other than components (A), (B), (C), (D), and (E). Examples of optional components include water-reducing agents, air-entraining agents, fluidizing agents, hardening accelerators (alkali stimulants), antifoaming agents, quick-setting additives, shrinkage-reducing agents, hardening retarders, and rust inhibitors. The hydraulic composition of the present invention may contain one or more of these optional components.
[0047] The hydraulic composition of the present invention can optionally contain cement, but the cement content must be carefully determined because it affects the initial hardening rate. Furthermore, from the perspective of providing a hydraulic composition with a reduced cement content, a lower cement content is preferable. The hydraulic composition of the present invention optionally contains cement, and the cement content may be less than 30 parts by mass, further 20 parts by mass or less, further 10 parts by mass or less, or even 1 part by mass or less, per 100 parts by mass of component (C). It may also be 0 parts by mass, i.e., no cement is contained. Examples of cement include Portland cement, white Portland cement, blended cement, ecocement, alumina cement, ultra-rapid hardening cement, grout cement, and oil well cement. The hydraulic composition of the present invention may have a Portland cement content within the above-mentioned range relative to component (C).
[0048] The hydraulic composition of the present invention may be a hydraulic composition comprising components (A), (B), (C), and predetermined amounts of components (D) and (E). In this case, the amount of each component can be selected from the range of the content indicated for each component, with the total amount of the components in the composition being 100 parts by mass. The hydraulic composition of the present invention may be a composition for geopolymers.
[0049] The hydraulic composition of the present invention can be produced by mixing components (A) to (E). There are no particular limitations on the order in which the components are mixed. The present invention provides a method for producing a hydraulic composition by mixing components including (A), (B), (C), (D), and (E), in which component (D) is mixed in an amount of 0.5 to 50 parts by mass per 100 parts by mass of component (B). The amounts of components (A) to (E) mixed in this production method can be selected from the contents described for the hydraulic composition of the present invention.
[0050] <Method of manufacturing the hardened body> The present invention relates to a method for producing a hardened product, which comprises curing the hydraulic composition of the present invention to obtain a hardened product. The method for producing the hardened product of the present invention can be appropriately applied to the matters described for the hydraulic composition of the present invention.Specific examples and preferred examples of the components (A) to (E) in the method for producing the hardened product of the present invention are the same as those for the hydraulic composition of the present invention.
[0051] The method for producing the hardened body of the present invention includes: step (I) of mixing components including (A), (B), (C), (D), and (E) to obtain a hydraulic composition, in which component (D) is mixed in an amount of 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of component (B); Step (II) of curing the hydraulic composition to obtain a hardened body; The components (A) to (E) are the same as those of the hydraulic composition of the present invention.
[0052] The amounts of components (A) to (E) mixed in step (1) can be selected from the contents described above for the hydraulic composition of the present invention. The hydraulic composition obtained in step (I) may be the hydraulic composition of the present invention. In step (I), the method, apparatus, conditions, etc. for mixing the components (A) to (E) are not particularly limited, and can be appropriately selected based on the method, apparatus, and conditions suitable for preparing a slurry.
[0053] In step (II), the hydraulic composition obtained in step (I) is cured to obtain a hardened product. The curing in step (II) can be performed under general conditions for obtaining a hardened geopolymer product. In step (II), the curing temperature can be, for example, 20°C or higher, further 30°C or higher, further 40°C or higher, and 80°C or lower, further 70°C or lower. In step (II), the curing time can be, for example, 1 hour or longer and 8 days or shorter. [Example]
[0054] The components used in the examples and comparative examples are shown below. (A) Ingredients: Mountain sand (produced in Joyo, Kyoto City, surface dry specific gravity 2.54, coarse particle ratio 2.73, amorphousness 1.1%, sphericity 0.86, average particle size 0.6 mm, bone dry condition) (B) Ingredient: Sodium metasilicate nonahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (C) Component (C-1): Ground blast furnace slag (blaine specific surface area: 4,200 cm 2 / g, alumina / silica molar ratio = 0.25) (C-2): Fly ash (JIS Type II, Blaine specific surface area: 3,500 cm 2 / g, alumina / silica molar ratio = 0.26) (D) Component (D-1): Potassium bicarbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (D-2): Sodium bicarbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Component (D') (comparison component of component (D)) (D'-1): Sodium hydroxide (Fujifilm Wako Pure Chemical Industries, Ltd.) (D'-2): Sodium carbonate (Fujifilm Wako Pure Chemical Industries, Ltd.) (E) Ingredients: Tap water (Wakayama City tap water)
[0055] <Examples and Comparative Examples> (1) Preparation of hydraulic composition and its hardened body The components (A), (B), (C), (D), (D'), and (E) were added to a Hobart mixer according to JIS R 5201 in the parts by mass shown in Table 1, and mixed at 140 rpm for 180 seconds to prepare hydraulic compositions for the Examples and Comparative Examples.
[0056] (2) Liquidity assessment The mortar flow of the hydraulic composition prepared as in (1) immediately after preparation was measured and recorded in accordance with JIS R 5201. The results are shown in Table 1.
[0057] (3) Strength evaluation Using the hydraulic composition prepared as described in (1) immediately after preparation, a mortar specimen of φ5 × 10 cm was prepared in accordance with JSCE-F 506, and after sealed curing at 20°C for 7 days, it was demolded and subjected to a compressive strength test in accordance with JSCE-G 505. The unconfined compressive strength (N / mm 2 The results are shown in Table 1. In the table, (D) / [(B)100] is the parts by mass of component (B) relative to 100 parts by mass of component (B).
[0058] [Table 1]
[0059] As can be seen from Table 1, Examples 1 to 4 exhibited superior fluidity and strength development compared to Comparative Examples 1 to 4. Even when a component capable of functioning as an alkaline irritant was used, as in Comparative Examples 2 and 3, it was found that both fluidity and strength could not be achieved, as with the bicarbonate of component (D) of the present invention. As mentioned above, this is believed to be due to the fact that the specified amount of component (D) used in the present invention reversibly immobilizes and releases calcium ions as calcium bicarbonate, which has relatively high solubility. This suppresses the decrease in fluidity of the hydraulic slurry associated with the rapid growth of CS(A)-H in the early stages of hydration, while intermittently releasing calcium ions as the material ages, accelerating the hydration reaction and achieving strength development of the hardened body. Furthermore, even when component (D) of the present invention is used, if the (D) / [(B)100] ratio is outside the range of the present invention, as in Comparative Example 4, fluidity is reduced and the hydraulic composition hardens insufficiently.
Claims
1. A hydraulic composition containing (A) fine aggregate (hereinafter referred to as component (A)), (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder (hereinafter referred to as component (C)), (D) bicarbonate (hereinafter referred to as component (D)), and (E) water, wherein the content of component (D) is 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of component (B).
2. 2. The hydraulic composition according to claim 1, wherein the component (A) is at least one selected from the group consisting of river sand, land sand, mountain sand, sea sand, lime sand, silica sand, blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, natural lightweight fine aggregate, and recycled fine aggregate.
3. 3. The hydraulic composition according to claim 1 or 2, wherein the component (C) is at least one selected from the group consisting of ground granulated blast furnace slag, fly ash, metakaolin, rice husk incineration ash, coconut shell incineration ash, municipal waste incineration ash, and sewage sludge incineration ash.
4. 3. The hydraulic composition according to claim 1, wherein the component (B) is at least one selected from the group consisting of water glass, sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.
5. 3. The hydraulic composition according to claim 1 or 2, which optionally contains cement, and the content of the cement is less than 30 parts by mass per 100 parts by mass of the component (C).
6. The hydraulic composition according to claim 1 or 2, wherein the content of the component (D) is 0.1 parts by mass or more and 4.0 parts by mass or less per 100 parts by mass of the hydraulic composition.
7. A method for producing a hydraulic composition comprising mixing (A) fine aggregate, (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder, (D) bicarbonate (hereinafter referred to as component (D)), and (E) a component containing water, wherein component (D) is mixed in an amount of 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of component (B).
8. A process for obtaining a hydraulic composition by mixing components including (A) fine aggregate, (B) metasilicate (hereinafter referred to as component (B)), (C) fine alumina-silica powder, (D) hydrogencarbonate (hereinafter referred to as component (D)), and (E) water, in which component (D) is mixed in an amount of 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of component (B); A step (II) of curing the hydraulic composition to obtain a hardened body; A method for producing a cured body, comprising: